Cultural dimensions as key aspects to change and improve school performance: a qualitative study in the Brazilian public schools - Oliveira, Pedro Henrique de; Almada Santos, Fernando César; Paschoalotto, Marco Antônio Catussi; Delmônico, Diego Valério de Godoy [UNESP]; Terence, Ana Cláudia Fernandes [UNESP] (Emerald, 2023)
Purpose: Despite the school organizational culture broad literature, there is still a gap on culture and educational management, mainly in the public environment. To fill out this space, this article wants to point out the cultural factors that creates school management change in the Brazilian public school context. Design/methodology/approach: The sample is a polar multi-case approach with two high performance and two low performance Brazilian schools. The authors conducted 12 interviews, three each school, with school principal, pedagogical coordinator and administrative officer. To analyze the data, the authors applied synthetic analysis to identify the cultural factors and your conduciveness to change in schools. Findings: The results point out organizational culture as low understood in public municipal schools. These results also indicate the cultural dimensions power distance, uncertainty avoidance, individualism, masculinity, long-term orientation and indulgence as influencers of school management. Therefore, organizational culture is a factor to change and improve performance in public school management. Research limitations/implications: Despite the low comprehensiveness by the school managers, the authors pointed out the importance of the cultural factors, such as power distance, uncertainty avoidance, individualism, masculinity, long-term orientation and indulgence, in the school management. Future research could assess quantitatively the cultural factors presented here. Social implications: The paper provides cultural aspects in the school environment that should be considered in the school management improvement process and school principals’ actions. Originality/value: The results fulfil the gap of organizational culture and school management in the public sector studies, by pointing out cultural factors of change in the school environment.
Keywords: Cultural change; Cultural dimensions; Organizational culture; School management; School performance